Ethical Dilemmas of Artificial Intelligence and Human Employment Rights (International Journal of Scientific Research in Science and Technology, 2025)
Artificial Intelligence (AI) has become one of the most transformative technologies of the twenty-first century. Its rapid integration into industries such as manufacturing, healthcare, finance, transportation, and communication has significantly increased productivity and efficiency. However, the widespread adoption of AI also raises complex ethical challenges, particularly regarding human employment rights. Automation systems increasingly perform tasks that were once carried out by human workers, creating concerns about job displacement, economic inequality, labor rights, and social justice. This paper examines the ethical dilemmas associated with AI-driven automation and its impact on employment. It analyzes key issues such as job displacement, the right to work, technological inequality, and the dignity of labor. The study also evaluates real-world examples of automation and discusses policy recommendations such as reskilling initiatives, ethical AI development, and stronger labor protections. The paper argues that while AI has the potential to enhance economic growth and innovation, governments and organizations must ensure that technological advancement does not undermine human welfare and employment rights. A balanced approach that combines technological progress with ethical responsibility is necessary for sustainable and inclusive economic development.